Implementasi Penggunaan Wi-Fi dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Fiqih di MAN 2 Blitar - Najmi Diny Hasnamahiroh; Mochamad Nasichin Al Muiz (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The decrease in student enthusiasm for learning at MAN 2 Blitar is caused by the limited physical references in the madrasah library, thus hindering the expansion of students' knowledge. To overcome this, madrasas provide Wi-Fi facilities as an alternative learning medium to increase learning motivation, especially in fiqh subjects. This research uses a qualitative approach with a case study type. Data sources include Madrasah Heads, Curriculum Waka, Fiqh Teachers, and MAN 2 Blitar students. Data collection techniques are carried out through interviews, observations, and documentation. Data analysis used data reduction, data presentation, and conclusion drawing techniques, with the validity of the data tested through triangulation, extension of participation, and peer discussion. The focus of this research includes the urgency, implementation, and barriers and solutions for the use of Wi-Fi in increasing motivation to learn fiqh. The results show that the use of Wi-Fi is important because it can reduce the economic burden on students, facilitate the learning process, and create a varied and innovative learning atmosphere. The implementation of Wi-Fi is carried out through online article searches, the use of the Canva application for presentations and poster assignments, and the use of learning videos from YouTube. The obstacles faced include unstable networks, power outages, and misuse of internet access, which are overcome by the addition of routers, the provision of generators, as well as supervision and restrictions on the use of student devices.